Spatial and temporal 2H and 18O isotope variation of contemporary precipitation in the Bale Mountains, Ethiopia. Issue 2 (3rd March 2020) - Lemma, Bruk; Kebede Gurmessa, Seifu; Nemomissa, Sileshi; Otte, Insa; Glaser, Bruno; Zech, Michael
ABSTRACT: East Africa is an underrepresented region in respect of monitoring the stable isotopic composition of precipitation (δ 18 Oprec and δ 2 Hprec ). In 2017, we collected precipitation samples from ten weather stations located along an altitudinal transect ranging from 1304 to 4375 m a.s.l. The δ 18 Oprec and δ 2 Hprec values varied from –8.7 to +3.7 ‰ and –38 to +29 ‰, respectively. The local meteoric water line is characterised by a lower slope, a higher intercept and more positive d -excess values (δ 2 H = 5.3 ± 0.2 * δ 18 O + 14.9 ± 0.9) compared to the global meteoric water line. Both altitude and amount of precipitation clearly correlate with our isotope data. However, the δ 18 Oprec and δ 2 Hprec values show at the same time a seasonal pattern reflecting rainy versus dry season. More enriched isotope values prevailed shortly after the end of the dry season; more depleted isotope values coincided with high precipitation amounts recorded in May, August and September. Moreover, HYSPLIT trajectories reveal that during the dry season water vapour originates primarily from the Arabian Sea, whereas during the wet season it originates primarily from the Southern Indian Ocean. These findings challenge the traditional amount effect interpretation of paleoclimate isotope records from East Africa and rather point to a previously underestimated source effect.